The Effect of Digital Mareketing on MSME Income In Bandung Petshop Industry - Irsyad Kamal; Muhammad Aqshel Revinzky Nizar; Andreas Recki Prasetyo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
Businesses that are usually carried out using conventional methods such as trading that occur in the market are increasingly changing and are being replaced by a new lifestyle, namely online trading. One type of online trade that has occurred is trading through digital marketing. In the city of Bandung, there were 189 food and animal equipment shops. Of the 189 stores, 100 of them are MSMEs that already use digital marketing as a means of advertising. The method in this research using a sample paired t-test. Based on the t-count results are -5.063 and the significance value is 0.000 where it shows that the t-test value is below 0.05 which means there is a significant difference in sales before and after the implementation of digital marketing at animal shops in Bandung.